IN-FILL DESIGN IDENTIFICATION AS PRELIMINARY STUDY OF HERITAGE SITE CONSERVATION IN BOROBUDUR AREA - Dharma Putri, Pusparini Dharma Putri; Adishakti, Laretna Trisnantari (Built Environment Studies, 2024)
Hold a rural architecture atmosphere as their attribute, Borobudur Temple Compounds area facing urbanize impacts by massive development that threatened that attribute. Where this compounds has been registered as a World Heritage since 1995. The such as in social, political, and economic sectors, including architecture as well as regional layout. This issue becoming a big threat to the architecture preservation in the region. By using several parameters and virtual reconstruction as an identification tools, this research stand as an effort to preserve in the form of documentation. The process was carried out by directly visiting several villages in the Borobudur temple compound area and continued by conducting digital modeling and drawing. Most types of buildings have a gable roof but some deviations are found in a small part of the observed objects. This research identified the variety of infill design; space arrangements, construction structures, and aesthetic elements. On the other hand, this also a critics for government documentation and regulation regarding local architecture surrounding. This research final aimed to be positioned as a prelude to the data documentation stage in the Heritage Impact Assessment (HIA) process.